Student’s Persistence in The Pondok Lirboyo: A Mixed Methods Study - Muhammad Akhsanul Muhtadin; Manal Hendawi; Achmad Patoni; Ahmad Tanzeh (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This study seeks to identify the effect of internal components, such as (1) self-efficacy and (2) curriculum perceptions, as well as external factors, such as (3) institutional environment and (4) students' finances. This study employs a sequential model and a mixed-methods explanatory methodology, namely quantitative research followed by qualitative research. Based on Isaac Michael's methodology, this study's respondents were the Islamic boarding school (Pondok) and the students (santri) in Pondok Lirboyo, with a total sample size of 286. The analysis of this study employs multiple regression using the t-test and F-test, followed by the Determination Test (R2) to demonstrate the null hypothesis. The results of this study's analysis indicate that (1) there is a positive and significant direct effect on student persistence, (2) there is a positive and significant direct effect on curriculum perceptions on student persistence, (3) there is a positive and significant direct effect on the institutional environment on student persistence, (4) there is a positive and significant direct effect on student (santri) finance on student persistence, (5) there is a substantial regressive effect on student persistence, and (6) there is a substantial regressive effect on the student persistence.